Performance improvement for infiltration rate prediction using hybridized Adaptive Neuro-Fuzzy Inferences System (ANFIS) with optimization algorithms - Ehteram M.; Yenn Teo F.; Najah Ahmed A.; Dashti Latif S.; Feng Huang Y.; Abozweita O.; Al-Ansari N.; El-Shafie A. (Ain Shams University, 2023)
Fuzzy neural networks; Infiltration; Irrigation; Particle swarm optimization (PSO); Water management; Adaptive neuro-fuzzy inference; Cross sectional area; Infiltration opportunities; Infiltration process; Irrigation management; Optimization algorithms; Sine-cosine algorithm; Sustainable management; Fuzzy inference